The Effect of Mother's Knowledge about Child Supplementation on Giving Supplementation During the Covid-19 pandemic - Ratna Arifiana; Leila Nisya Ayuanda; Ely Krisnawaty (Urecol Journal. Part C: Health Sciences, 2022)
Covid-19 cases in the group of children in Indonesia are increasing, reaching around 11-12%. Covid-19 cases in children in Indonesia are the highest cases in the world. One of the efforts to prevent the transmission of COVID-19 in children is to increase immunity and health in children, which can be done by giving supplements to children. One of the factors that influence the provision of supplements to children is the mother's knowledge. This study uses quantitative analysis by analyzing the effect of the mother's level of knowledge about giving supplementation to children with supplementation to children. The subjects in this study were mothers who had children aged 0 months to 5 years. The sampling technique used was purposive sampling, so the number of samples in this study was 107 mothers. The instrument in this study used a questionnaire in the form of a google form which had been tested for validity and reliability. The result of this study is the influence of a mother's knowledge on the provision of supplementation to children with a p-value of 0.004. So health workers, especially midwives, have an important role in providing information to mothers and families to maintain health during the COVID-19 pandemic.